The Evolution of Ethnomathematics in Technology-Enhanced Learning in Indonesia - Jaka Wijaya Kusuma; Hamidah Hamidah; Puput Puspito Rini (International Journal of Science and Environment (IJSE), 2026)
This study examines the evolution of ethnomathematics in technology-based learning in Indonesia. The study's background highlights the importance of ethnomathematics in Indonesian education and the role of technology in modern learning. This study aims to analyse the integration of ethnomathematics in learning technology, identify specific patterns in technology adoption and adaptation, and reveal existing gaps in practice and research. The methodology used includes a comprehensive literature review and case descriptions. Cases were selected to provide an in-depth picture of how ethnomathematics manifests in daily activities and cultural practices, and how technology is integrated into the learning process. Key findings include patterns in the introduction and exploration of ethnomathematics through technology, the use of technology to connect mathematical concepts with local cultural contexts, and teachers' and students' adaptation of technology. Identified gaps include the gap between the potential of ethnomathematics and its actual implementation, as well as the gap between the availability of technology and its effective use. The study provides recommendations for the teaching practices of teachers, education policymakers, and technology developers, and identifies areas for further exploration in future research.